Otosclerosis and Stapes Surgery 2007
DOI: 10.1159/000098664
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Increased Average Age of Patients with Otosclerosis

Abstract: Otosclerosis is an inflammatory disease of the human temporal bone which was assumed to affect up to 10% of the Caucasians. Histologic otosclerosis has an incidence of 3.4%. It is considered as a major cause of hearing loss in Western countries while a low incidence is observed among Africans. Many hypotheses about its origin had been formulated in the past. Otosclerosis genes (OTSC1-5) and collagen 1 genes are mutated in some familial cases of otosclerosis. On this genetic background, a common environmental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…However, there have been conflicting results as in the study by Grayeli et al [49], which could not detect measles virus RNA in the otosclerotic bone. According to the study of Arnold et al [50] and Niedermeyer et al [51,52], anti-measles vaccination seems to be correlated with decreasing numbers of stapes surgery as well as increasing age of patients at the time of surgery. In conclusion, a great body of evidence suggests that otosclerosis is an inflammatory disease associated with persistent measles virus infection.…”
Section: Persistent Measles Virus Infection In Otosclerosismentioning
confidence: 97%
“…However, there have been conflicting results as in the study by Grayeli et al [49], which could not detect measles virus RNA in the otosclerotic bone. According to the study of Arnold et al [50] and Niedermeyer et al [51,52], anti-measles vaccination seems to be correlated with decreasing numbers of stapes surgery as well as increasing age of patients at the time of surgery. In conclusion, a great body of evidence suggests that otosclerosis is an inflammatory disease associated with persistent measles virus infection.…”
Section: Persistent Measles Virus Infection In Otosclerosismentioning
confidence: 97%
“…Whether it is a common phenomenon in otosclerosis requires a detailed study in a larger cohort of familial cases. It is worthwhile to mention that a retrospective study reported that the onset of otosclerosis may be delayed due to vaccination against measles, use of low-dose contraception drugs, and improved healthcare [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otosclerosis is a multifactorial disease, which progressively leads to the development of hearing loss and for which several theories have been proposed regarding its pathogenesis. Although it has been the focus of many studies in recent decades, the factors contributing to the onset and progression of the disease are not fully clear, and the main ones that have been associated are as follows: (a) genetic factors, (b) viral infections, (c) autoimmune mechanisms, (d) cytokines, and (e) hormonal factors [8][9][10][11][12][13][14][15][16][17].…”
Section: Etiopathogenesismentioning
confidence: 99%